Pengaruh Citra Negara Asal terhadap Keputusan Pembelian Mellaui Citra Merek (Studi pada Konsumen Mobil Wuling di Kota Semarang) - Hasmoro, Alexander Dio; Darmastuti, Ismi; Nurdianasari, Rista (Faculty of Economics and Business Diponegoro University, 2024)
ABSTRACT Sales of the car industry in Indonesia can be said to be growing rapidly in the last period. The car brand used as the object of this study is Wuling, which is a vehicle brand from Liuzhou, Guangzi, China. This brand is run by the Liuzhou Wuling Automobile Industry, Co., Ltd. company, which is a joint venture by Wuling Group and Dragon Hill Holdings Limited. This research was conducted in Semarang City which resulted in preresearch in the form of low purchasing decisions, namely there are indications of problems regarding the purchasing decisions of Wuling consumers in Semarang City in the indicators